KRITIK WACANA SEKSUALITAS PEREMPUAN - Munfarida, Elya (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2009)
as a discourse, knowledge about women sexuality embodies power relation by control, discipline and normalization. With thisperspective, interpretation about woman sexuality that represented by term that attributed to women are related with a political interest. Thismeaning normalized with values, norms, and social practice mechanism until truth about woman and their sexuality accepted as undeniabletruth. Phallucentric paradigm that becomes basis woman sexuality discourse is making man as interpretation subject. Therefore, womanpositioned as sexual object that understood and defined with man perspective and interest. Woman subordination that placed them aspassive figure sexually have making them loosing their sexual creativity and activity. This condition imply continuous social problem faced bywomen: sexual violence/harassment, trafficking, unhealthy sexual life, unwanted pregnancy, sexual infection,